Advancing Food Security in the Cryolithozone and Exploring Organic and Mineral Fertilizer Strategies for Enhanced Crop Yields - Gomadhi, G.; Dhanalakshmi, K.; Chitra, K.; Prabhavathi, S. Jaya; Gayathry, G.; Vidhya, D.; Malathi, G. (PLANT CELL BIOTECHNOLOGY AND MOLECULAR BIOLOGY, 2024)
The Cryolithozone, characterized by its frozen soil and harsh climatic conditions, presents unique challenges to agricultural productivity and food security. As global temperatures rise, the thawing of permafrost in the Cryolithozone offers opportunities for agricultural expansion but also raises concerns about soil degradation and nutrient loss. In this article, we explore innovative approaches to enhance crop yields and food security in the Cryolithozone, focusing on the integration of organic and mineral fertilizer strategies. We discuss the potential benefits and challenges of utilizing organic fertilizers, such as compost and manure, to improve soil fertility and mitigate nutrient deficiencies. Additionally, we examine the role of mineral fertilizers in supplying essential nutrients to crops in nutrient-deficient Cryolithozone soils. By synthesizing current research and best practices, we propose holistic fertilizer management strategies tailored to the unique environmental conditions of the Cryolithozone. These strategies aim to optimize nutrient utilization efficiency, minimize environmental impacts, and promote sustainable agricultural development in cold regions.